REVIEW STUDY OF THE ARTIFICIAL BREEDING OF GATTAN (Barbus xanthopterus, HECKEL) IN IRAQ - Al-Mukhtar, Mustafa A. (Iraqi Journal of Aquaculture, 2022)
This review article deals with the documentation of all the previous work on the propagation of Gattan. It was found that the induced spawning of Gattan is similar to that of common carp and Bunnei. The sensitive brooders needs a great care during handling and transportation. The brooders weight 5 were 1.5-10 kg for females and 1-2.5 kg for males, with age of 4-9 and 3-6 for the females and males respectively. The artificial breeding season continue from10 March till mid June. The MS222 was used for anesthesia with a concentration of 1/10000. Carp pituitary gland extract (CPG) was used in all the previous work, with different dosage wobbled between 3-6 mg/kg for females and 2-3 mg/kg for males. The total dosage was divided to 10 % for the first injection and 90 % for the second. The sex products was obtained after 12-14h from the second injection. The fertilized eggs were incubated in Zoug jars, at 23-25 ºC and water current of 0.5-0.7 l /min. The hatching was complete within three days. The larvae were reared in two stages the first in indoor incubators and the second in earthen ponds.